Two new species of Chiasmocleis Méhelÿ, 1904 from the Atlantic Rain Forest of southern Bahia, Brazil (Amphibia, Anura, Microhylidae) - Caramaschi, Ulisses (Arquivos do Museu Nacional, 2021)
Two new species of the genus Chiasmocleis from the Atlantic Rain Forest of southern Bahia, Brazil, are described. Both species belong to the group characterized by well-developed webbing on feet, composed until now by C. capixaba and C. leucosticta. Information on the habits of the new species and on the distribution of the genus in the biome are presented and discussed.